Implementasi Sistem Penjualan Online Produk Olahan dan Buah Nanas Berbasis Website - Muhammad Irfan Alfajri; Amir Luthfi; Deddy Gusman (Universitas Pahlawan Tuanku Tambusai, 2021)
Pineapple processed products are processed products of SMEs engaged in the production and sale of typical food kualu nenas village, mining subdistrict, Kampar regency, Riau province. The sales, marketing, and promotion system still uses the system manually, whereby the buyer must come directly to the store. Therefore, a website-based sales system will be created to develop pineapple processed products using php programming language and mySQL database online better known as E-Commerce (Electronic Commerce). With the methodology used in the design of this system is using the waterfall method. The advantages in this website-based sales system is that it can make it easier for consumers to make the process of buying transactions online which can save time and costs compared to buying come directly to the store.